Baseline characteristics of 547 new onset heart failure patients in the PREFERS heart failure study - Cecilia Linde; Mattias Ekström; Maria J. Eriksson; Eva Maret; Håkan Wallén; Patrik Lyngå; Ulla Wedén; Carin Cabrera; Ulrika Löfström; Jenny Stenudd; Lars H. Lund; Bengt Persson; et al. (ESC Heart Failure, 2022)
Abstract Aim We present the baseline characteristics of the PREFERS Stockholm epidemiological study on the natural history and course of new onset heart failure (HF) aiming to improve phenotyping focusing on HF with preserved left ventricular ejection fraction (HFpEF) pathophysiology. Methods and results New onset HF patients diagnosed in hospital or at outpatient HF clinics were included at five Stockholm hospitals 2015–2018 and characterized by N‐terminal pro brain natriuretic peptide (NT‐proBNP), biomarkers, echocardiography, and cardiac magnetic resonance imaging (subset). HFpEF [left ventricular ejection fraction (LVEF) ≥ 50%] was compared with HF with mildly reduced LVEF (HFmrEF; LVEF 41–49%) and with HF with reduced LVEF (HFrEF; LVEF ≤ 40%). We included 547 patients whereof HFpEF (n = 137; 25%), HFmrEF (n = 61; 11%), and HFrEF (n = 349; 64%). HFpEF patients were older (76; 70–81 years; median; interquartile range) than HFrEF (67; 58–74; P < 0.001), more often women (49% vs. 30%; P < 0.001), and had significantly higher comorbidity burden. They more often had atrial fibrillation, hypertension, and renal dysfunction. NT‐proBNP was lower in HFpEF (896; 462–1645 ng/L) than in HFrEF (1160; 563–2370; P = 0.005). In HFpEF, left ventricular (LV) diameters and volumes were smaller (P < 0.001) and septal and posterior wall thickness and relative wall thickness higher (P < 0.001). E/é ≥ 14 was present in 26% of HFpEF vs. 32% of HFrEF (P = 0.017) and left atrial volume index > 34 mL/m2 in 57% vs. 61% (P = 0.040). HFmrEF patients were intermediary between HFpEF and HFrEF for LV mass, LV volumes, and RV volumes but had the highest proportion of left ventricular hypertrophy and the lowest proportion of elevated E/é. Conclusions Phenotype data in new onset HF patients recruited in a broad clinical setting showed that 25% had HFpEF, were older, more often women, and had greater comorbidity burden. PREFERS is well suited to further explore biomarker and imaging components of HFpEF pathophysiology and may contribute to the emerging knowledge of HF epidemiology. Clinical trial registration: Clinicaltrials.gov identifier: NCT03671122.